The Impact of Negative Goodwill Accounting on Entity's Financial Performance - Grzybek , Olga (Studia Oeconomica Posnaniensia, 2018)
The aim of the article is to analyze the impact of negative goodwill accounting on the financial situation of an entity. The excess of net assets fair value over cost is either a bargain purchase gain or negative goodwill, defined as future expenses that are not individually identified on the date of acquisition. The economic substance of the excess depends on the circumstances of its arising and should not be forced with the accounting law. The author made a simulation and analysis of a financial statement for 5 alternative ways of accounting for negative goodwill. IFRS 3 allows entities to create a very positive image. Presenting bargain purchase gain as other comprehensive income would limit the risk of erroneous interpretation for the users of financial statements.